Fatigue Life Prediction of Submarine Pipelines with Varying Span Length and Position - Daoyu Jiang; Xiaowei Huang; Deping Zhao; Haijing Yang; Guoqiang Tang (Journal of Marine Science and Engineering)
Free spans of submarine pipelines are prone to be subjected to vortex-induced vibration (VIV) under the action of currents, leading to fatigue damage of submarine pipelines. In the traditional method, the fatigue damage is predicted assuming that the length of free span is a constant. However, the free-span length may vary in time and space due to local scour and sand wave migration in engineering practice. This study proposed probabilistic methods to predict the fatigue life of the free spans by considering the effect of variant span length and span position. Truncated Gaussian, Raileigh and Uniform distributions of span length due to local scour, and a sinusoidal pattern with a constant migration rate is assumed for the sand wave due to the lack of field scan data. The fatigue life of a 120 m long span under a constant current-induced flow with the velocity of 0.7 m/s has been assessed. Results show that comparing with the fatigue life of a fixed span, the present method leads to an increase in the fatigue life by about ten times.